2014
DOI: 10.3892/mmr.2014.2795
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin: An adipokine activator of rat hepatic stellate cells

Abstract: The present study was conducted to investigate the effects of visfatin on the activation of hepatic stellate cells (HSC) and the possible underlying mechanism. HSC were isolated from the livers of Sprague‑Dawley rats by in situ perfusion of collagenase and pronase and a single‑step density Nycodenz gradient. The culture‑activated cells were serum‑starved and incubated with different concentrations of recombinant visfatin (0, 25, 50, 100 or 200 ng/ml) for 24 h. The expression of α‑smooth muscle actin (α‑SMA), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The progressive accumulation of fibrosis is the hallmark of NASH disease progression 1 . Liang et al 52 . reported that visfatin upregulated the gene and protein production of α‐SMA, a marker of HSC activation, and increased the mRNA and protein expression of collagen types I and III in the rat HSC.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive accumulation of fibrosis is the hallmark of NASH disease progression 1 . Liang et al 52 . reported that visfatin upregulated the gene and protein production of α‐SMA, a marker of HSC activation, and increased the mRNA and protein expression of collagen types I and III in the rat HSC.…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin is an adipocytokine, which has an insulinlike effect, can promote nicotinamide adenine dinucleotide synthesis, and is involved in mediating inflammation and immunity (23)(24)(25). In recent years, studies have shown that visfatin can stimulate tumorigenesis and metastasis by stimulating inflammatory mediators and proinflammatory cytokines that are involved in tumor development (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…These cells release IL-6 and TNF in high quantity, and this is further induced by visfatin [ 161 ] ( Figure 2 ). In hepatic stellate cells synthesis of α‑smooth muscle actin, collagens and connective tissue growth factor are induced by visfatin, indicating profibrotic activity of this cytokine [ 162 ] ( Figure 2 ). In line with this in vitro study, an in vivo analysis shows reduced hepatic collagen and α‑smooth muscle actin upon suppression of hepatic visfatin in tetracarbon chloride and ethanol-treated rodents [ 163 ].…”
Section: Adipokines In Liver Cirrhosismentioning
confidence: 99%